(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Due to the situation caused by the Covid-19 pandemic, biobanks have adapted, among other processes, the obtaining of informed consents (IC). This paper details the most relevant elements of the applicable regulations, describes the adaptations done by some of the biobanks of the Spanish Biobank Network to manage the IC process, which have been approved by their Ethics Committees, and draws some conclusions from the results obtained from the survey carried out on these biobanks.